2012
DOI: 10.1134/s187537281201012x
|View full text |Cite
|
Sign up to set email alerts
|

Classification of river basins and hydrological regionalization (as exemplified by Japan)

Abstract: A set of problems related to formation of areas homogeneous in hydrological aspect is considered. A methodology of regionalization is proposed. New analytical methods of the methodology are intended of solving such problems as (i) the problem of regionalization and (ii) the problem of constructing of a classification for river drainage basins. Efficiency of the methods proposed has been tested on the problems, which arise in the process of constructing classifications for river drainage basins, and also on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…This method originates from the Voronoi diagrams (Aurenhammer 1991) assuming that at any point in the watershed, the rainfall value is equal to the weighted mean of the nearest rain gauges, being possible to trace the areas of influence of the stations to characterize the spatial variability of rainfall (Souza et al 2017). These variables are easily obtained and are commonly used in streamflow regionalization studies (Gubareva 2012, Xu et al 2014, Elesbon et al 2015.…”
Section: Data Selection and Processing Criteriamentioning
confidence: 99%
“…This method originates from the Voronoi diagrams (Aurenhammer 1991) assuming that at any point in the watershed, the rainfall value is equal to the weighted mean of the nearest rain gauges, being possible to trace the areas of influence of the stations to characterize the spatial variability of rainfall (Souza et al 2017). These variables are easily obtained and are commonly used in streamflow regionalization studies (Gubareva 2012, Xu et al 2014, Elesbon et al 2015.…”
Section: Data Selection and Processing Criteriamentioning
confidence: 99%
“…Eschen et al, 2014) and other fields (e.g. Laize and Hannah, 2010;Gubareva, 2012). Indeed, Roige (2017) found that HC performed best using a number of statistical metrics when compared with SOMs and kmeans for clustering pest assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…Типизация геосистем речных бассейнов, выполненная с учетом морфологии рельефа, может служить для различных целей: оценки эрозионной опасности [Smirnova et al, 2015], агроэкологического [Krupkin, 2007;Dunaeva, Kovalenko, 2013], гидрологического [Gubareva, 2012], геоэкологического районирования [Mineev et al, 2017] и др.…”
Section: Introductionunclassified
“…По мнению ряда исследователей, выделение однородных гидрологических районов продиктовано необходимостью не только оценки условий неизученных бассейнов по аналогии с изученными, что особенно актуально в условиях недостаточно плотной сети наблюдений, но и выявления фундаментальных географических закономерностей строения и функционирования речных систем [Gubareva, 2012]. Объединение бассейнов-аналогов в группы, сходные по динамике развития, обусловливает необходимость выделения из общего количества репрезентативных объектов, которые могут служить для более детального исследования природно-антропогенных динамических процессов и дальней-шего экологического мониторинга [Trifonova et al, 2009].…”
Section: Introductionunclassified